One-Year, Multicenter, Open-Label, Single-Arm Study Evaluating the Safety and Effectiveness of Etanercept for the Treatment of Moderate-to-Severe Plaque Psoriasis in a Canadian Population. Issue 2 (March 2013) - Vender, Ronald; Lynde, Charles; Gilbert, Martin; Ho, Vincent; Sapra, Sheetal; Poulin-Costello, Melanie
Background: Although etanercept is well tolerated and effective in moderate-to-severe plaque psoriasis, data are limited in Canadian practice settings. Objective: To assess the effectiveness and safety of etanercept in Canadian patients with moderate-to-severe plaque psoriasis (Physician Global Assessment [PGA] ≥ 3) in routine practice. Methods: A 1-year, multicenter, open-label trial of 246 patients enrolled from March 2006 to July 2009 was conducted. Patients received etanercept 50 mg subcutaneously twice weekly for 3 months and then 50 mg once weekly for 9 months. The primary end point was the proportion of patients achieving a PGA score ≤ 2 at month 12. Secondary end points included the proportion of patients achieving PGA score ≤ 2 at months 3, 6, and 9 and change from baseline at month 12 for Patient Global Assessment (PtGA), body surface area, and Dermatology Life Quality Index (DLQI). Adverse events were reported. Results: At month 12, 73.5% (95% CI 67.2–79.1) achieved a PGA score ≤ 2. The response was similar regardless of the previous response to systemic or phototherapy. The proportion of patients achieving this score improved from 2.2% (95% CI 0.3–4.2) at baseline to 73.5% (95% CI 67.2–79.1) at 12 months. At 12 months, patients with a DLQI score of 0 or ≥ 5-point improvement was 28.8% (95% CI 22.9–34.7) and 47.3% (95% CI 40.8–53.9), respectively. No new safety signals were reported. Conclusion: The majority of this Canadian population demonstrated a meaningful improvement in PGA and DLQI scores over 1 year.